PENELUSURAN MINAT BACA KARYA SASTRA PROSA MAHASISWA SEMESTER VII PRODI BAHASA INDONESIA IKIP SILIWANGI CIMAHI - Rudi Awici; Aji Raga Pamungkas; Diena San Fauziya (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This study aims to decry reading interest prose literature on semester VII students Prodi Bahasa Indonesia IKIP Siliwangi Cimahi. The method used in this research is descriptive method. This method is used to analyze reading interest: the feeling of reading, the purpose of reading, reading habits, reading desire, reading barriers, and the reason to read prose literature on the students of semester VII Prodi Bahasa Indonesia IKIP Siliwangi Cimahi. The sample used in this study is the students of semester VII of Indonesian Language Study Program IKIP Siliwangi Cimahi selected randomly with the number of 31 respondents. The instrument used for this research is a questionnaire instrument. Reading feeling value of 0,79 or 79%. The reading goal value of 0,76 or 76%. Values of reading habits and desires of 0,71 or 71%. The value of desire and looking for reading material of 0,76 or 76%. The reason for reading prose literature is for entertainment, adding insight, and because of the demands of the task. Meanwhile, the obstacles that arise in the activity of reading is because busy, lazy, and sleepy. Favorite prose mentioned by the respondents are Dilan 1990 by Pidi Baiq, Laskar Pelangi by Andrea Hirata, and Fiersa Besari's Konspirasi Alam Semesta.